Myonecrosis in Sickle Cell Anemia—Overlooked and Underdiagnosed - Nishant Tageja; Marius Racovan; Jason Valent; Jeffrey Zonder (Case Reports in Medicine)
Medical literature detailing muscular complications of sickle cell anemia is sparse and limited to a few case-reports. Features consistent with myositis and myonecrosis are often overlooked and patients are inadequately treated, leading to unforeseen complications. We report an interesting case of sickle cell myonecrosis and review the existing literature on this subject.